Analisis Penerapan Sistem Gustodian terhadap Kualitas Sistem Pengendalian Internal di New Sunari Lovina Beach Resort. - Fedani, Meya Aca; Dewi, Nyoman Ayu Wulan Trisna; I Made Dwita Atmaja (Vokasi : Jurnal Riset Akuntansi, 2025)
This research is motivated by the need for hotels to improve the effectiveness and efficiency of financial management through information technology. The purpose of the study is to analyze the implementation of the Gustodian System on the quality of the internal control system at New Sunari Lovina Beach Resort. The approach used is qualitative with interview, observation, and documentation methods in five divisions: accounting, front office, housekeeping, food & beverages service, and Arishta SPA. The results of the study indicate that the Gustodian System improves transparency, accountability, and trust between divisions. This system also provides accurate data for competitive analysis, shortens operational time, and minimizes the risk of human error. In terms of monitoring and auditing, the system facilitates transaction tracking and supports internal audits. Real-time access to information also helps faster and data-based decision making. This research provides a practical contribution to hotel management and the hospitality industry.